Three Adventures of Sherlock Holmes - "Conan, Doyle Arthur " (Longman Group Ltd: China, 1996)
Sherlock Holmes is a great detective. There are few cases that he cannot solve. In these three stories we meet a young woman who is terrified of a mysterious "speckled band", a family who think five orange pips are a sign of death, and a banker who believes that his son is a thief. But are things really as they seem to be?
Keywords: Detective and mystery stories-English